Social Factors of Ecology Influencing City Governance and Development - Kholmirzaev Nodirjon Nizomjonovich (Central Asian Journal of Theoretical and Applied Science, 2022)
The article discusses issues such as the problem of clean drinking water, waste, epidemics, salinization of the land, excessive air pollution.